Pengaruh Model Pembelajaran E-learning Berbantuan Media Pembelajaran Edmodo Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik - Hanifah Hanifah; Nanang Supriadi; Rany Widyastuti (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2019)
Mathematical problem solving is a problem solving that uses mathematical problem solving. Students in the problem solving did not use the polya method so that students succeeded in difficulties. Educators still use conventional learning models so that students become bored, passive and reluctant to ask whether going forward working on the questions given by the educator, so that new learning models need to be applied. The e-learning learning model assisted with Edmodo learning media is an online presentation material on an Edmodo account using the mobile phone of students. PAM is the knowledge learned by students before getting learning material. This study aims to study the interaction of e-learning learning models assisted by Edmodo learning media to solve mathematical problems. This study is quantitative research. Data collection used with tests, interviews, collection and collection. The data analysis technique uses two-way anava test with cells that are not the same. From the results of the analysis, the influence of the e-learning learning model on mathematical problem solving abilities. It is necessary to question the high, medium, and low mathematical initial knowledge of Great mathematical problem solving ability, then there is no difference between assisted e-learning learning models edmodo, mathematical initial knowledge of mathematical problem solving abilities.